Crystal structure of (1α,2β,3α,4β,5α,12α,13β,14α, 15β,16α,17β,18α,25α,26β)-N-(2-methoxyethyl)-5, 12,18,25-tetraphenyl-27,28,29,30-tetraoxadeca-cyclo-[14.10.1.1 3,14.15,12.118,25.04,13.0 6,11.017,26 - Wang, S. (2014)
Zeitschrift fur Kristallographie - New Crystal Structures